Enriching governance in Africa via sustainable tourism - the integrity action pathway - Agwa, Samuel (Strathmore University, 2014)
The lofty human interchange and economic potential of tourism poses a critical platform and frontier with boundless possibilities that could be harnessed to enrich the quality of governance in Africa at both State and non-State levels. The tourism and hospitality industry has a socially enriching depth that beyond building communities, saving nature and sustainable biodiversity abounds with adaptable integrity considerations that can be weaved within its theoretical and operational demonstrations to generally add value to deepening governance via personal and organisational integrity actions. This could be realisable by tapping into rich nature‟s lessons as well as general insightfulness in turning recreation and leisure to deeper moments of self-retreats and reminiscences. The far reaching depth of how a refreshing tourism experience could be transformed to an inspirational and uplifting integrity challenge or action for the industry stakeholders to seek and apply sustainable common good pursuits back to the workplace is reasonably highlighted. An incisive out of the box straitjacket is addressed beyond peering at nature and holidaying clasping the wine glass of hospitality. Though thinking integrity or considering its significance may not be the primary pursuits in a tourism experience or plan, distantly distinct scenarios have been elicited to create an integrity-tourism synergy that within sustainable tourism re-programming and overhaul could have resounding promise for deepening governance and public policy.
Conference paper presented at the 1st African Conference on Sustainable Tourism in Strathmore University, Kenya.
Keywords: Sustainable tourism; Governance; Africa